STRUKTUR KEPRIBADIAN TOKOH UTAMA DALAM NOVEL LAYANGAN PUTUS KARYA MOMMY ASF - Al Aini, Nadya Zulfa; Pramulia, Pana (Jurnal Bahastra, 2023)
The part of the soul that exists in human existence as a unit that is not divided in the explanatory function of personality. Understanding personality means understanding me, myself, myself or the whole person. Sigmund Freud's psychoanalysis is that a person's life is largely controlled by the subconscious mind. Many behaviors are based on unconscious desires, impulses, urges, and so on. Repressed desires and urges live on in the subconscious, always seeking satisfaction. Sigmund Freud's Personality Structure Although it expresses different technical concepts, the basic concept is the same. That is, human behavior is more determined and controlled by the subconscious mind than his personality. The novel Layangan Putus by Mommy ASF tells the story of the struggle of a woman who has given birth to 4 children, when her husband Kinan abandoned her fifth pregnancy with another woman and Kinan's fifth child with Aris died after being born. For 12 days Aris went missing without a word from another woman. Apparently, the news that Kinan received at that time was that her husband Aris had been practicing polygamy with another woman. The part of the soul that exists in human existence as a unit that is not divided in the explanatory function of personality. Understanding personality means understanding me, myself, myself or the whole person. Sigmund Freud's psychoanalysis is that a person's life is largely controlled by the subconscious mind. Many behaviors are based on unconscious desires, impulses, urges, and so on. Repressed desires and urges live on in the subconscious, always seeking satisfaction. Sigmund Freud's Personality Structure Although it expresses different technical concepts, the basic concept is the same. That is, human behavior is more determined and controlled by the subconscious mind than his personality. The novel Layangan Putus by Mommy ASF tells the story of the struggle of a woman who has given birth to 4 children, when her husband Kinan abandoned her fifth pregnancy with another woman and Kinan's fifth child with Aris died after being born. For 12 days Aris went missing without a word from another woman. Apparently, the news that Kinan received at that time was that her husband Aris had been practicing polygamy with another woman.